1998
DOI: 10.1017/s0950268898001058
|View full text |Cite
|
Sign up to set email alerts
|

The 1993 dengue 2 epidemic in Charters Towers, North Queensland: clinical features and public health impact

Abstract: In 1993 an epidemic caused by dengue virus type 2 occurred in several North Queensland population centres. Charters Towers, estimated population 10,000, had 155 officially notified cases. An analysis of symptoms was undertaken using a random sample of 1000 residents to determine specificity of symptoms, the subclinical infection rate, and to establish the true extent of the epidemic. Retrospective diagnoses of dengue fever were based on the presence of both serum dengue 2 neutralizing antibody and presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 20 publications
(17 reference statements)
2
27
1
Order By: Relevance
“…In addition, whilst data on previous travel or residence in Northern Queensland was not specifically collected, seroprevalence could be attributed to previous exposure to dengue or other local flaviviruses, such as Kunjin or Murray Valley encephalitis virus. There is conflicting data on age and gender association with dengue seroprevalence in non-endemic countries [30,33] and whilst over two-thirds of the travellers with evidence of past dengue infection were older than the median age of the current cohort, the association between age and seroprevalence was not found to be significant. DHF has been described infrequently in travellers and there are no studies reporting on the incidence of DHF in travellers [9][10][11].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, whilst data on previous travel or residence in Northern Queensland was not specifically collected, seroprevalence could be attributed to previous exposure to dengue or other local flaviviruses, such as Kunjin or Murray Valley encephalitis virus. There is conflicting data on age and gender association with dengue seroprevalence in non-endemic countries [30,33] and whilst over two-thirds of the travellers with evidence of past dengue infection were older than the median age of the current cohort, the association between age and seroprevalence was not found to be significant. DHF has been described infrequently in travellers and there are no studies reporting on the incidence of DHF in travellers [9][10][11].…”
Section: Discussionmentioning
confidence: 96%
“…The 20 travellers with pre-existing antibodies for dengue infection in the current study did not report a past history of dengue infection. The rates of clinical-to-subclinical infection identified in studies of local endemic populations have ranged from 1:0.2 to 1:7 [30][31][32], and the determinants of clinical versus subclinical infection are not clearly defined. Infecting DENV strains, cross-reactive immunity from infection with different DENV serotypes and pre-existing host immunity may play a role.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, taste alteration was reported as a dengue predictor by the few researchers who investigated this symptom [15,39], and conjunctival redness was reported by Low et al . [15] as one of the most accurate signs (p < 0.0005; OR = 4.49) for dengue diagnosis among adult outpatients with a fever lasting less than 72 hours.…”
Section: Discussionmentioning
confidence: 99%
“…It is recognized that asymptomatic infections are thought to be uncommon, at least in adult Caucasian and Asian populations. 5,6 However, several studies have shown that the rate of asymptomatic infections can be much higher in the pediatric population. 7 Since the 1960s, millions of people have been affected by DF, and many have died as a consequence of DHF.…”
Section: Introductionmentioning
confidence: 99%